THE FALL OF SAWAHLUNTO (Studi tentang Pengaruh Gejolak Ekonomi-Politik Global terhadap Perkembangan sebuah Kota Lokal, 1930-1940an) - Dedi Arsa (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2018)
Sawahlunto is a mining town that enjoyed the glory due to coal exploitation by the Dutch colonial government which began in the 1880s. But in the early 1930s to the end of the 1940s, triggered by successive world economic crises (malaise) and various political upheavals during and some time after the Pacific War, this city has experienced a number of long downturns. This paper looks at the effect of economic decline and political turmoil on a city, in this case the City of Sawahlunto as a mining city. Using modern historical methods (historiography, interpretation, interpretation and writing), with an approach to the history of the city, this article reveals several things: First, in the 1930s, due to the world's crisis, coal production was dimming, this caused no new development of the city. Second, in 1942 the Pacific War took place, Japan ruled over the mining company, and Sawahlunto became worse off. Third, after Indonesia gained its independence until the end of the 1960s, Sawalunto did not receive significant improvements, except for a few rebuilt infrastructures. Thus, economic sluggishness and political riot at the global [and national] level have had a direct influence on a city at the local level.